Eleições presidenciais de 2014: uma análise das agendas programáticas - Lima, Bárbara (Universidade Federal de São Carlos, 2015)
In the current Brazilian political scenario the political propaganda are at the center of political practices. Such centrality is enhanced during the election period. This is when the political parties launch candidates who present their platform of government. The Horário Gratuito de Propaganda Eleitoral (HGPE) is the central element of the campaigns and main device by which the candidates establish direct communication and mobilize their electorate. In this scenario, the electoral programs broadcasted on television are still the primary sources of information and it is essential among the uncertain scenario that "time policy" promotes among citizens (Veiga, 2002). Due the importance and the centrality the advertisements and the media exercise in electoral periods, the objective is to analyze the construction of the programmatic agenda of the main running parties (PSB, PT and PSDB) through the analysis of government programs presented to TSE and propagandas aired in HGPE for presidential elections in 2014.
The presidential election of 2014: an analysis of the programmatic agendas
Keywords: Eleições; Campanha eleitoral; Propaganda; Agenda programática; Elections; Electoral campaign; Programmatic agenda; CIENCIAS HUMANAS::CIENCIA POLITICA